Books Completed or in Progress by Academy Members (Academy of Management Journal, 1963)
The article presents a list of books related to management. They include “Accounting in Small Business Decisions,” by W. Warren Haynes and James L. Gibson, “Human Elements of Administration: Cases, Readings, and Simulation Exercises,” by Harry R. Knudson, and “The Management of Scientific Research,” by Louis G. Strasburg.